If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -1 + 7(x + 1) = -1(6x + -5) Reorder the terms: -7x + -1 + 7(1 + x) = -1(6x + -5) -7x + -1 + (1 * 7 + x * 7) = -1(6x + -5) -7x + -1 + (7 + 7x) = -1(6x + -5) Reorder the terms: -1 + 7 + -7x + 7x = -1(6x + -5) Combine like terms: -1 + 7 = 6 6 + -7x + 7x = -1(6x + -5) Combine like terms: -7x + 7x = 0 6 + 0 = -1(6x + -5) 6 = -1(6x + -5) Reorder the terms: 6 = -1(-5 + 6x) 6 = (-5 * -1 + 6x * -1) 6 = (5 + -6x) Solving 6 = 5 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 6 + 6x = 5 + -6x + 6x Combine like terms: -6x + 6x = 0 6 + 6x = 5 + 0 6 + 6x = 5 Add '-6' to each side of the equation. 6 + -6 + 6x = 5 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 5 + -6 6x = 5 + -6 Combine like terms: 5 + -6 = -1 6x = -1 Divide each side by '6'. x = -0.1666666667 Simplifying x = -0.1666666667
| 17=2+y | | 2x^3-11x^2+10x+8=0 | | 0=x^2-10x+21 | | 7m+3n-7(7m-6n)= | | 7m-3=2(5m-2)+16 | | x*x+5x=12 | | 2+4y=-14 | | 6y+20=7x | | 3(-1)+y=5 | | 8x-3x+2x-9x= | | 3(1)+y=5 | | -9+3x+5x=-33 | | x+1+3x=-19 | | 1/4(8x-40) | | 3(x-4)=37-4x | | r^2+14=9r | | 24(34+r)=1248 | | 2x-5=75-8x | | -30=-7x-x+2 | | 9x+5=2x+54 | | Y-5=2(x-4) | | -2x-9+3x=-19 | | 13+5+6y+y-2= | | 2(-1)-y=1 | | -4x-3+5x=-3 | | 2(n+3)=-4 | | 2(0)-y=1 | | Y+8=-2(x-3) | | 6n+1=-13 | | -3x-7x=60 | | a/3-3=6 | | 2(2)-y=1 |